The Mouse Island Marathon - Geronimo Stilton
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. Each book is a fast-paced adventure with lively art and a unique format kids 7-10 will love. I admit it. I'm not much of a muscle mouse. So when I accidentally got signed up for the Mouse Island Marathon, I was so shocked that I lost my squeak! Me, run a marathon? But my friends and family were determined to help me cross that finish line. Holey cheese, I was never going to make it!